Educational Platformer Game (OOP-EduGame) to Enhance Student Motivation and Understanding in the Object Oriented Programming Subject - Azhar Ahmad Smaragdina; Ahmad Mursyidun Nidhom; Dila Umnia Soraya; Gres Dyah Kusuma Ningrum; Muhammad Iqbal Akbar (Association for Scientific Computing Electrical and Engineering, 2020)
The Object-Oriented Programming (OOP) course aims to impart understanding and knowledge to students regarding basic-level object-oriented programming concepts and the implementation of inheritance, encapsulation, and polymorphism. This subject contains abstract concepts that require a high level of understanding and also a sufficiently strong memory which often makes students feel bored. We consider the need for a learning innovation that can boost student learning motivation and also make it easier for them to understand and remember abstract concepts in OOP material. Based on these problems, we plan to use games in learning activities. Games are a potential tool to support learning activities [1], where games can provide great motivation for students to play [2]. Furthermore, games are one of the 3 most popular applications in Southeast Asia[3], where this data is also confirmed by the Global Mobile Consumer Survey which shows that 47% of the population in Southeast Asia play games through their smartphones. Mobile game applications are also proven to be able to contribute to learning outcomes and student learning motivation. After conducting a review of the literature and analyzing related research, we think that the educational game application can be used theoretically as a solution to the problems we have described. This application is available anytime and anywhere that allows students to look deeper into the materials and to offer a virtual learning environment that is not restricted by the time and place to work together and share ideas for solving programming problems. The educational game that we developed is called OOP-EduGame, this game is a platformer game genre that is one of the most popular game genres. The development method for this application uses the ADDIE model. The results of validation from experts and the responses from users as a basis for measuring the readiness of the application for use in learning activities are also presented.